Effectiveness of a Self-instructional Booklet for Healthy Eating Habits of School Students - Rajeswari, V. (International Journal of Nursing Research, 2023)
Aim of the Study: The aim of the study was to determine whether the self-instructional booklet made any change in the knowledge and practice with regard to healthy eating habits of middle schoolchildren. Materials and Methods: The conceptual framework used in this study was based on a modified effectiveness model. The independent variable was the self-instructional booklet, and the dependent variables were knowledge and practice on healthy eating habits. The study was conducted in a selected government school, Sulur, Coimbatore. The pre-test was conducted by giving a self-administered knowledge questionnaire and practice checklist to 60 students in the various age categories and selected by systematic random sampling technique. After the pre-test, orientation was given to the students regarding the purpose of the study, and the self-instructional booklet was issued to the students and asked them to read the booklet and practice the diet provided in the booklet. After 25 days, post-test was conducted using the same self-administered questionnaire and checklist to the same group of students. Results: The data were analyzed using descriptive and inferential statistics. The result of the study showed that before the intervention overall mean knowledge score regarding eating habits was 8.366 (41.83%), whereas after the intervention, the mean knowledge score had increased to 14.97 (74.85%). Statistically, there has been a considerable difference between the mean knowledge score on eating habits before and after the intervention. Before the intervention, the mean practice score regarding healthy and unhealthy eating habits was 8.3 (83%), whereas after the intervention, the mean practice score had slightly increased to 9.85 (98.5%). Statistically, there was a significant difference between the mean practice score on eating habits before and after the intervention. Conclusion: This study concluded that there was a significant increase in the mean knowledge score and mean practice score of eating habits after the intervention.